Endringer i lærerstudenters kompetanser? En casestudie fra en ny lærerutdanning ved UiT Norges arktiske universitet - Olufsen, Magne; Karlsen, Solveig; Ødegaard, Marianne (Naturfagsenteret, 2017)
Source at http://dx.doi.org/10.5617/nordina.3140 From 2017 the Norwegian teacher education in primary and lower secondary school will be a five-year master education. UiT - The Norwegian Arctic University started a master education already in 2010. The main differences between the old and new program are: increased credits in both pedagogy and the master subject, more emphasize on pedagogical content knowledge (PCK) and more focus on the master subject early in the education. In this case study, teacher supervisors evaluate students’ knowledge in their school practice. All teacher supervisors in the study with practice from both former and new education, experienced that the master students had increased subject matter knowledge and PCK. These changes in preservice teacher knowledges can possibly be explained by changes in the education program. Our results show that early emphasize on subject, increased focus on PCK and subject matter knowledge are important features in the development of the pre-service teachers’ professional knowledge.